An exploratory study of the extent of social inclusion among people with psychosis and psychotic-related conditions. (May 2017) - Turner, Niall; Ferguson, Lisa; Hill, Michele; Nesbitt, Tara; O'Callaghan, Eadbhard; O'Mahony, Paul; Clarke, Mary
Background: Understanding social inclusion among at-risk populations will deepen our understanding of their specific needs. Aim: This study explored the level of social inclusion among people with psychotic-related conditions using a standardised interview. Method: The Social Inclusion Interview Schedule was used in two research projects. People with psychosis participated in both studies and had been recruited as part of an Irish programme of research on psychotic conditions. Descriptive statistics were used to quantify participants' level of social exclusion. Results: Data from 71 participants were available, 38 in one cohort and 33 in the other. The smaller cohort had a shorter mean duration of illness. Participants' mean age was 40. The majority lived in the community and were satisfied with their living arrangements. In each cohort, the same two areas of community integration emerged as problematic – having something productive to do and being close to someone in the community. There was a higher level of perceived stigma among the cohort with the longer duration of illness. Discussion/Conclusion: While evidence of social inclusion was found among participants, there were areas of concern particularly with regard to integration into work and social connectedness.